Performance of a Magnesium-Rich Primer on Pretreated AA2024-T351 in Full Immersion: a Galvanic Throwing Power Investigation Using a Scanning Vibrating Electrode Technique - Geraint Williams (Journal of The Electrochemical Society, 2018)
The scanning vibrating electrode technique (SVET) was employed to examine the effect of ‘galvanic throwing power’ and the distance over which a Mg-rich primer (MgRP) provided sacrificial anode-based cathodic protection to AA2024-T351. Three systems were investigated in full immersion conditions where the same MgRP was used with three different pretreatments: Non-film forming (NFF), trivalent chromium pretreatment (TCP) and anodization with a chromate seal (ACS). Experiments were conducted with two coating/defect area ratios and three parameters were monitored: 1) the maximum peak height of local anodes, inferring the location and intensity of pits, 2) the current density profile at the coating/defect interface (CDI) region and 3) total integrated anodic and cathodic current density values of defined areas in the defect region moving progressively away from the CDI. The NFF-based system was shown to provide the superior galvanic throwing power and a quasi-steady-state galvanic current distribution was detected in the defect region adjacent to the CDI indicating enhanced cathodic activity in response to the MgRP. High resistance between the MgRP and the substrate, due to the thickness of the pretreatment layer, appeared to mediate galvanic interactions in the case of TCP and ACS-based systems.